Cell death induced by cytotoxic CD8+ T cells is immunogenic and primes caspase-3–dependent spread immunity against endogenous tumor antigens. Issue 1 (1st April 2020) - Jaime-Sanchez, Paula; Uranga-Murillo, Iratxe; Aguilo, Nacho; Khouili, Sofia C; Arias, Maykel A; Sancho, David; Pardo, Julian
Abstract : Background: Elimination of cancer cells by some stimuli like chemotherapy and radiotherapy activates anticancer immunity after the generation of damage‐associated molecular patterns, a process recently named immunogenic cell death (ICD). Despite the recent advances in cancer immunotherapy, very little is known about the immunological consequences of cell death activated by cytotoxic CD8 + T (Tc) cells on cancer cells, that is, if Tc cells induce ICD on cancer cells and the molecular mechanisms involved. Methods: ICD induced by Tc cells on EL4 cells was analyzed in tumor by vaccinating mice with EL4 cells killed in vitro or in vivo by Ag-specific Tc cells. EL4 cells and mutants thereof overexpressing Bcl-XL or a dominant negative mutant of caspase-3 and wild-type mice, as well as mice depleted of Tc cells and mice deficient in perforin, TLR4 and BATF3 were used. Ex vivo cytotoxicity of spleen cells from immunized mice was analyzed by flow cytometry. Expression of ICD signals (calreticulin, HMGB1 and interleukin (IL)-1β) was analyzed by flow cytometry and ELISA. Results: Mice immunized with EL4.gp33 cells killed in vitro or in vivo by gp33-specific Tc cells were protected from parental EL4 tumor development. This result was confirmed in vivo by using ovalbumin (OVA) as another surrogate antigen. Perforin and TLR4 and BATF3-dependent type 1 conventional dendritic cells (cDC1s) were required for protection against tumor development, indicating cross-priming of Tc cells against endogenous EL4 tumor antigens. Tc cells induced ICD signals in EL4 cells. Notably, ICD of EL4 cells was dependent on caspase-3 activity, with reduced antitumor immunity generated by caspase-3–deficient EL4 cells. In contrast, overexpression of Bcl-XL in EL4 cells had no effect on induction of Tc cell antitumor response and protection. Conclusions: Elimination of tumor cells by Ag-specific Tc cells is immunogenic and protects against tumor development by generating new Tc cells against EL4 endogenous antigens. This finding helps to explain the enhanced efficacy of T cell-dependent immunotherapy and provide a molecular basis to explain the epitope spread phenomenon observed during vaccination and chimeric antigen receptor (CAR)-T cell therapy. In addition, they suggest that caspase-3 activity in the tumor may be used as a biomarker to predict cancer recurrence during T cell-dependent immunotherapies.